2000
DOI: 10.1053/joca.1999.0311
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage damage after intraarticular exposure to collagenase 3

Abstract: Activated MMP-13 leads to tissue collagen damage with the release of collagen fragments. These fragments are measurable and could provide a method for assessment of cartilage collagen damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…In vivo studies with animal models have confirmed the role of MMP-13 in osteoarthritis (OA) progression. In one of these studies, Otterness and coworkers injected active human recombinant MMP-13 intra-articularly into the knee joint of hamsters (Otterness et al, 2000). Collagen cleavage was limited to a thin superficial band at the cartilage surface, probably because of the strong binding of the hemopexin-domain for collagen and gelatin.…”
Section: Neoplastic Diseasesmentioning
confidence: 99%
“…In vivo studies with animal models have confirmed the role of MMP-13 in osteoarthritis (OA) progression. In one of these studies, Otterness and coworkers injected active human recombinant MMP-13 intra-articularly into the knee joint of hamsters (Otterness et al, 2000). Collagen cleavage was limited to a thin superficial band at the cartilage surface, probably because of the strong binding of the hemopexin-domain for collagen and gelatin.…”
Section: Neoplastic Diseasesmentioning
confidence: 99%
“…An antibody that selectively recognizes the C-terminal neoepitope generated by collagenase (MMP 1, MMP 8, MMP 13, or MT1-MMP) cleavage of collagen I, II, or III (9A4 antibody) was used at a concentration of 14 g/mL. [22][23][24] Endothelial cells were detected by biotinylated Griffonia (Bandeiraea) Simplicifolia Lectin-I (GSL, Vector Laboratories; 100 g/mL). For quantitative analysis of immunoreactive cleaved collagen, measurements were performed with the use of Image-Pro software (Media Cybernetics) to calculate the percentage of total area stained positive.…”
Section: Histologymentioning
confidence: 99%
“…[22][23][24] For each animal, the area stained was quantified by averaging 10 random high-power fields from the infarct area. There was no difference in the areas of cleaved collagen between vehicle and MMPitreated groups by image analysis, indicating that fibrillar collagen cleavage was not inhibited by MMPi (Figure 4).…”
Section: Mmp Inhibition Selectivitymentioning
confidence: 99%
“…Some employ trypsin, stromelysin, and MMPs. [11][12][13] Others use cytokines such as IL-1. 14 The problem with these approaches is that they lack specificity.…”
Section: Introductionmentioning
confidence: 99%